(untitled) - Arasaki, Seibin (Tokyo, 1983)
Likes land plants, sea vegetables contain photosynthetic pigments and develop by means of photosynthesis performed using the sun's rays.
Keywords: Marine algae as food,Tảo biển làm thức ăn